Relationship between motivation of Women of Reproductive Age (WRA) and husband's support with participation in visual inspection with acetic acid examination of WRA - Kiki Andari; Sunarsih Sunarsih; Anggraini Anggraini; Nita Evrianasari (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Visual Inspection Test with Acetic Acid (VIA Test) is a cervical cancer screening method using a 3-5% acetic acid solution on the cervix. The impact that arises if women do not conduct early detection of cervical cancer is usually cervical cancer detected at an advanced stage. Many factors are associated with the participation of mothers to participate in the VIA test, including factors influenced by motivation and husband support. Purpose: The purpose of this study was to determine the relationship between WRA motivation and husband support with the participation of Visual Inspection with Acetic Acid (VIA Test) examination in WRA. Method: Quantitative research type case control study design. The population of this study were all women of childbearing age in the Blambangan Pagar Health Center Working Area of North Lampung Regency in 2025, with a total of 2436 women of childbearing age aged 30-50 years with a sample of 55 respondents using proportional sampling method. Data collection using questionnaire sheets, univariate and bivariate data analysis (chi square). Results: The results of univariate research showed that of the 55 respondents where the respondents had performed VIA examination as many as 11 (20.0%) and respondents never participated in conducting VIA examination as many as 44 (80.0%), respondents with strong motivation as many as 15 (27.3%) and respondents with weak motivation as many as 40 (72.7%), and respondents with husband support as many as 21 (38.2%) and respondents with no husband support as many as 34 (61.8%). Conclusion: The bivariate test found that there was a relationship between motivation (p-value = 0.001) and husband support (p-value = 0.014) with the participation of VIA examination in WRA. Suggestion: Suggestions for husbands to be able to seek information in various media such as print media, electronic media about VIA examination, and from health workers can provide counseling about the benefits of VIA examination so that it can motivate mothers to do VIA examination.